Preparation and Characterization of A New Nano-scaled Material Composed of Bentonite-Polyethylenglycophthalate - Nagim, Omer Kareem; Himdan, Takialdin Abdulhadi; Abuzaid, Yousif Ibrahim Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study a new composite material have been prepared and characterized through polymerization of ethylene glycol located between the Bentonite layers with phthalic anhydride. The results showed that the polymer binds with the structure of clay through hydrogen bonding also the polymerization process led to shatter of the three-dimension crystal structure of the clay and isolating layers in the form of nano-scale two-dimensional sheets, the polymer growth around the clay isolated layers work to increase the size particles at microscopic scale.